2017
DOI: 10.1007/s11356-017-9496-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon degradation potential and plant growth-promoting activity of culturable endophytic bacteria of Lotus corniculatus and Oenothera biennis from a long-term polluted site

Abstract: Many endophytic bacteria exert beneficial effects on their host, but still little is known about the bacteria associated with plants growing in areas heavily polluted by hydrocarbons. The aim of the study was characterization of culturable hydrocarbon-degrading endophytic bacteria associated with Lotus corniculatus L. and Oenothera biennis L. collected in long-term petroleum hydrocarbon-polluted site using culture-dependent and molecular approaches. A total of 26 hydrocarbon-degrading endophytes from these pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 73 publications
4
37
0
Order By: Relevance
“…Due to absorption of easily degradable hydrocarbons in the plant roots, the superior hydrocarbons removal was observed during the initial 30 days of the experiment in T2 treatment. These results are in agreement with the finding of previous research [39,40]. The literature study revealed that in spite of microorganisms, the degradation of hydrocarbons is also assisted by plants that play a fundamental role by taking up the hydrocarbons in their roots and shoots and change them into less harmful substances [41,42].…”
supporting
confidence: 93%
“…Due to absorption of easily degradable hydrocarbons in the plant roots, the superior hydrocarbons removal was observed during the initial 30 days of the experiment in T2 treatment. These results are in agreement with the finding of previous research [39,40]. The literature study revealed that in spite of microorganisms, the degradation of hydrocarbons is also assisted by plants that play a fundamental role by taking up the hydrocarbons in their roots and shoots and change them into less harmful substances [41,42].…”
supporting
confidence: 93%
“…Pawlik et al examined the potential for hydrocarbons degradation (diesel oil, n -hexane and p -xylene degradation) of endophytic bacteria isolated from Lotus corniculatus and Oenothera biennis growing in contaminated soil [ 47 ]. Isolated endophytes belonged mainly to the genera of Pseudomonas, Stenotrophomonas, Rhizobium, and Rhodococcus .…”
Section: Resultsmentioning
confidence: 99%
“…Isolated endophytes belonged mainly to the genera of Pseudomonas, Stenotrophomonas, Rhizobium, and Rhodococcus . Over 90% of them were able to utilize diesel oil as a carbon source [ 47 ]. Also, Philips et al studied the degradation abilities of endophytes isolated from the prairie plants.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the presence of ryegrass was shown to stimulate the expression of bacterial PAH-ring hydroxylating dioxygenase genes, such as nidA3, pdoA, nahAc and phnAc (Guo et al, 2017a,b). Several Lotus corniculatus (common bird's-foot trefoil) and Oenothera biennis (common evening primrose) root endophytes belonging to the genera Rhizobium, Pseudomonas, Stenotrophomonas and Rhodococcus harbored genes encoding for CYP153 alkane hydroxylases and showed the capacity to grow with n-hexadecane as sole source of carbon (Pawlik et al, 2017). Other plants, such as Achillea millefolium (yarrow), Soligado canadensis (Canadian goldenrod), Trifolium aureum (hop clover) and Dactylis glomerata (orchard grass), growing in a heavily contaminated site, harbored hydrocarbon-degrading bacterial endophytes mostly belonging to the Actinobacteria (Lumactud et al, 2016).…”
Section: Microbes As Hydrocarbon Degradersmentioning
confidence: 99%